The Influence of the Principal's Leadership Style on Teacher Performance in Elementary Schools in Gugus Hagasta, Sirimau District, Ambon City - Desembra Sohilait (International Journal of Education, Information Technology, and Others, 2022)
This study aims to determine the effect of leadership style (X1) on teacher performance (Y), either individually or jointly. This research was conducted in elementary schools in the Hagasta Cluster, Sirimau District, Ambon City, amounting 10 schools, using a correlational research design, it means that the research examined the influence of independent variables with the dependent variable. The population of the research is the teachers of 10 elementary schools in the Hagasta Cluster, Sirimau District, Ambon City wich is 144 people. The sampling technique is proportional randomized sampling or random sampling by taking into account the proportion of the number of teachers for each school in order to obtain as many as 30 people to sample the test and 105 people to sample of the research. Based on these results, the researchers concluded that the variations that occur in the teacher's performance at SD Gugus Hagasta, Sirimau District, Ambon City in is affected by a wide variety of leadership styles but work stress has no influence. Evidently, the leadership style either individually or jointly are variables that contributed most to the performance of elementary school teacher in the amount of 0,51% . It means that to improve the performance of elementary school teachers can be reached by improving a good leadership style, wich is good so that it can improve the performance of teacher in national education